A Case of Bullet Injury of Spine - Gurung, Dipendra; Sherchan, Binod; Khadka, Nilam (Nepal Journal of Neuroscience, 2017)
Available with full text. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 25-27